Bibliometric Analysis of Medical Specialization Theses on Health Literacy in Turkey (Turkey Health Literacy Journal, 2022)
Objective: In this study, it was aimed to determine the tendencies and neglected aspects of the theses by evaluating the medical specialty theses related to health literacy (HL) in Turkey with the bibliometric analysis method. Method: Medical specialty theses published between 1967-2021 in the National Thesis Center (https://tez.yok.gov.tr/UlusalTezMerkezi), which is the thesis database of the Council of Higher Education, were scanned with the keywords “Health Literacy” and “Literacy”. The 82 theses reached were examined according to various variables (year, scale, research method, universe, etc.). Results: 57% of theses were made by family medicine, 33% by public health and 10% by other branches. It was determined that 46% (n=38) of theses were made in the adult population without a specific feature, and 26% (n=21) were made in adult patients who were diagnosed. There is no thesis about immigrants. The most frequently used scale in theses is TSOY-32 (Turkish Health Literacy Scale-32) (%44, n=36) and the most frequently used research method is the cross-sectional research method. It has been determined that the theses evaluating certain subjects and groups with specific scales were made in 2018 and later. Conclusion: There is a need to increase the interest of other branches in the subject and not to ignore disadvantaged groups in studies. In order not to make mistakes in comparing studies, consensus on a single scale can be recommended in the assessment of general health literacy. Considering the tendency of health literacy to become specific, it is clear that it is a concept open to development. There is a need for new studies in this regard, especially in neglected aspects.